Steroid Hormone Sensitivity in Reproductive Mood Disorders: On the Role of the GABAA Receptor Complex and Stress During Hormonal Transitions - Schweizer-Schubert, Sophie; Gordon, Jennifer L.; Eisenlohr-Moul, Tory A.; Meltzer-Brody, Samantha; Schmalenberger, Katja M.; Slopien, Radoslaw; Zietlow, Anna-Lena; Ehlert, Ulrike; Ditzen, Beate (Frontiers in Medicine, 2021)
Women worldwide are two to three times more likely to suffer from depression in their lifetime than are men. Female risk for depressive symptoms is particularly high during the reproductive years between menarche and menopause. The term “Reproductive Mood Disorders” refers to depressive disorders triggered by hormonal fluctuations during reproductive transitions including the perimenarchal phase, the pre-menstrual phase, pregnancy, the peripartum period and the perimenopausal transition. Here we focus on reproductive mood disorders manifesting in adult life. We propose a research agenda that draws together several reproductive mood disorders and investigates which genetic, endocrinological, neural and psychosocial factors can explain depressive symptoms during phases of hormonal transitions in women. Based on current research it is assumed that some women experience an increased sensitivity to not only fluctuations in reproductive steroids (estrogen and progesterone), but also stress-related steroids. We integrate both dynamics into the concept of “steroid hormone sensitivity”, expanding on the concept of “reproductive hormone sensitivity”. We suggest that a differential response of the stress steroid system including corticosteroids, neurosteroids, like allopregnanolone and the GABA-A Receptor complex, as well as a differential (epi)genetic risk in serotonergic and GABAergic signaling, are moderators or mediators between changes in the reproductive steroid system and the physiological, affective and cognitive outcomes manifesting in reproductive mood disorders. We point to the lack of research on the role of psychosocial factors in increasing a woman’s stress level and at some point also the sensitivity of her stress steroid system within the etiology of Reproductive Mood Disorders. Drawing together the evidence on various reproductive mood disorders we seek to present a basis for the development of more effective pharmacological, social and psychological treatment interventions and prevention strategies for women susceptible to these disorders. This could pave the way for new research as well as medical and psychological teaching and practice- such as a new type of Practice for Gynecological Psychoneuroendocrinology- with the aim of working on and ultimately offering more integrative forms of support not yet available to women suffering from depression during hormonal transitions. In medical history women have been left alone with this integrative challenge.